The importance of moving average convergence divergence as a part of indicators in technical analysis for the Malaysian stock market / Mohd Firdaus Mohd Aripin - Mohd Aripin, Mohd Firdaus (Faculty of Business and Management, 2009)
There are two methods to analyze Malaysia stock market: Fundamental and Technical. Technical analysis is a very powerful tool and is a pre-requisite for anyone who wants to predict financial market movements and build successful trading system. Technical indicators, collectively called "technicals", are distinguished by the fact that they do not analyze any part of the fundamental business, like earnings, revenue and profit margins. Technical indicators look to predict the future price levels, or simply the general price direction, of a security by looking at past patterns. Examples of common technical indicators include Relative Strength Index (RSI), Money Flow Index, Stochastics, Moving Average Convergence Divergence (MACD) and On Balance Volume (OBV). The MACD is the common indicator used by the trader. The MACD is a versatile indicator giving clear buy and sell signals and giving warnings of impending price changes.